Development of Professional Competency of Managerial Staff on the Basis of Acmeological Approach - SHTAL, Tatyana V.; LYTOVCHENKO, Iryna; POLIAKOVA, Hanna A. (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).35, 2018)
Currently, there is a change in the role of education in the direction of forming a vector of continuing education, cultivation of self-development skills, self-organization in order to improve the professional competences of management. The article examines the need to reorganize the existing education system at enterprises and formation of new technologies of development of professional competences of managerial staff. It is proved that the main objective of the competence approach in vocational education is the formation of a competent managerial specialist with appropriate competence sets needed for successful achievement of an organization's strategic goals. The acmeological aspects of professional competence of managerial staff with the use of basic acmeology categories are discussed in details. The process of development and application of archeological technologies at domestic enterprises is proposed. The theoretical and methodological basis of the research was: the principles of system, integrity, unity and mutual determination of the external and internal. As theoretical methods, theoretical-methodological and retrospective analysis, generalization and interpretation of scientific data were used.